Antimicrobial activity study of ethanolic extract of Boerhaavia diffusa whole plant (International Journal of Pharmacy and Life Sciences, 2012)
The search for antimicrobial agents has continued to be concentrated on the lower plants, fungi and bacteria. Less research has focused on higher plants although identified plant compounds like emetine, berberine quinine still find specialized uses. Secondary metabolites of higher plants serve as defense agent against microorganisms. Some screenings have yielded good result and few of these have proceeded to give active antimicrobial compounds like polygodial, anethol, himejima, crytolepine, etc. The present work is carried out on the Boerhaavia diffusa whole plant on the basis of the literature obtained from the Ethno medicinal documentation. The common name is Punarnava and it is found wild throughout India mostly in Himalayan valleys. Keeping in view the tremendous ethno medicinal use of Boerhaavia diffusa it was aimed to scientifically validate the antimicrobial property of Boerhaavia diffusa whole plant.